Forest fragments in urban matrices: a conservation network for Atlantic Forest birds - Carlos Eduardo Zimmermann; Jonas Raimundo Fuchs; Laio Zimermann Oliveira; Rosemeri Carvalho Marenzi; Joaquim Olinto Branco (Acta Scientiarum. Biological Sciences, 2024)
Fauna conservation in anthropic ecosystems is crucial. This study aimed to assess the role of forest fragments in protecting bird communities within the urban matrix of Blumenau, state of Santa Catarina, Brazil. Bird species were identified using visual and auditory methods across five forest remnants from January 2016 to December 2019. Fieldwork began in the early morning and covered both the interior and edges of the areas. The relationship between species richness and land use within the forest fragments and adjacent matrices was investigated to support management actions for expanding urban landscapes. These actions are necessary as habitats and corridors may be eliminated, leading to reduced landscape connectivity. The results indicate an interaction between fragment size and land use, which contributes to the formation of environmental mosaics in the urban landscape. These mosaics may influence bird species richness and composition. Effective public management of legally unprotected forest remnants, regardless of size, along with permanent preservation areas (e.g., riparian forests and urban green spaces) and conservation units, may strengthen a network of green areas for protecting and conserving Atlantic Forest bird species in urban environments.